Implementasi Contextual Teaching and Learning (CTL) untuk Meningkatkan Minat Belajar Matematika Siswa Sekolah Dasar - Darfi Widiarni; Ezif Rizqi Imtihana (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2026)
This study aims to analyse the implementation of Contextual Teaching and Learning (CTL) in mathematics learning and to explore students' learning interest at SDN Sumberharjo Pacitan. A qualitative case study design was employed (Yin, 2018; Creswell, 2014), as this study seeks to understand a real-life phenomenon, namely CTL implementation, in its natural context without manipulating variables. Data were collected through semi-structured in-depth interviews using an interview guide with one classroom teacher, one school principal, and eleven Grade IV students (6 males and 5 females; aged 9–10 years); participant observation using an observation checklist across four learning sessions on quadrilateral topics; and documentation of lesson plans, student worksheets, activity photographs, and field notes. Data were analysed using the Miles–Huberman–Saldaña interactive model (data condensation, data display, and conclusion drawing/verification) and validated through source and technique triangulation. The results reveal that CTL was applied systematically through seven components: constructivism, inquiry, questioning, learning community, modelling, reflection, and authentic assessment. The findings indicate that students demonstrated increased learning interest across four dimensions: affective (positive feelings and enthusiasm), cognitive (contextual understanding through real-life examples), behavioral (collaborative engagement in group discussions), and motivational (a sustained desire to continue learning independently). Three mediating factors underlie the effectiveness of CTL, namely teacher role transformation, content contextualisation, and institutional support. This study contributes a three-factor mediating framework that connects the effectiveness of CTL to Vygotsky's Zone of Proximal Development (ZPD), Bruner's representational theory, and Hidi–Renninger's four-phase model of interest development.